Injectable Polypeptide‐Protein Hydrogels for Promoting Infected Wound Healing. (4th May 2020) - Cheng, Liang; Cai, Zhengwei; Ye, Tingjun; Yu, Xiaohua; Chen, Zhijie; Yan, Yufei; Qi, Jin; Wang, Lei; Liu, Zhihong; Cui, Wenguo; Deng, Lianfu
Abstract: Protein is the key composition of all tissues, which has also been widely used in tissue engineering due to its superior biocompatibility and low immunogenicity. However, natural protein usually lacks active functions such as vascularization, osteo‐induction, and neural differentiation, which limits its further applications as a functional biomaterial. Here, based on the mimetic extracellular matrix feature of bovine serum albumin, injectable polypeptide‐protein hydrogels with vascularization and antibacterial abilities are constructed successfully via coordinative cross‐linking of sulfydryl groups with silver ions (Ag+) for the regeneration of infected wound. In this protein hydrogel system, (Ag+), acting as crosslinkers, can not only provide a sterile microenvironment and a strong and robust antibacterial ability but also introduce K2 (SL)6 K2 (KK) polypeptide, which endows the hydrogel with vascularization behavior. Furthermore, the in vivo data show that the polypeptide‐protein hydrogel has a considerable collagen deposition and vascularization abilities in the early stage of wound healing, resulting in rapid new tissue regeneration featured with newly appeared hair follicles. Altogether, this newly developed multifunctional 3D polypeptide‐protein hydrogel with vascularization, antibacterial properties, and hair follicle promotion can be a promising approach in biomedical fields such as infected wound healing. Abstract : Polypeptide‐protein hydrogels are designed and developed for promoting infected wound healing. Through coordinative cross‐linking of thiolated bovine serum albumin protein and thiolated vascular polypeptide with silver ions, the gels obtain additional vascularization and antibacterial activities that can accelerate infected wound healing. The hydrogel is highly promising as a novel protein‐based biomaterial for biomedical applications.